Statin Function as an Anti-inflammation Therapy for Depression in Patients With Coronary Artery Disease by Downregulating Interleukin-1β. Issue 2 (February 2016) - Ma, Wenlin; Shen, Dan; Liu, Jie; Pan, Jiangqi; Yu, Lu; Shi, Weiqi; Deng, Liang; Zhu, Lingfeng; Yang, Fan; Liu, Junjun; Cai, Wenping; Yang, Jianhua; et al.
Abstract : Abstract: It is well known that inflammation contributes to the development of coronary artery disease (CAD) and depressive symptoms. Previous studies have shown that long-term application of statin reduces the occurrence of depression in patients with CAD. However, the mechanism remains unclear. We hypothesized that inflammation contributes to depression in patients with CAD and statin function as an anti-inflammation therapy for those depressive patients. Patients with confirmed CAD hospitalized in the Department of Cardiology of Tongji Hospital in Shanghai, China, were enrolled. Depression was identified as none (ND), mild (MiD), moderate (MoD), or severe (SD) on the basis of scores of the patient health questionnaire with 9 items. Inflammatory factors in peripheral blood were measured using a chemiluminescence immunoassay and Bio-plex. Luciferase expression level was detected using the Dual-Luciferase Reporter Assay System for IL-1β or NF-κB expression by transfection in human umbilical vein endothelial cells, and patient serum was added. Data obtained from 217 patients with CAD were analyzed. The IL-1β level of CAD with SD was 14.70, which was significantly higher than that of CAD with ND 7.52, MiD 7.73, or MoD 8.63. Luciferase reporter gene analysis showed that IL-1β or NF-κB expression level was upregulated by the serum of CAD and depression patients. After the addition of atorvastatin, IL-1β or NF-κB luciferase reporter expression level decreased. It suggested that depression in patients with CAD is associated with inflammation. Statin may function as an anti-inflammation therapy for depression in patients with CAD by downregulation of IL-1β.